Diola ang bayani ng Philippine eagle ina ni Pag-Asa at Pagkakaisa = Heroine of Philippine eagles : mother of "Pag-Asa" and "Pagkakaisa" - Ordinario, Mary Ann (ABC Educational Development Center, 2018)
Diola was a rescued Philippine Eagle that was raised in Monkey Eating Eagle Rehabilitation City in Davao City. She brought the Philippines recognition for being the first country to ever successfully hatch an egg from an eagle through artificial means. Diola was the mother of Pag-asa and Pagkakaisa.--Pumplepie: Books & Happiness.